Key Issues for Primary Schools - Farrell, Michael (Routledge, 1999)
Key Issues for Primary Schools is a concise comprehensive guide to the main issues in primary education and the implications for schools. Presented in a convenient A-Z format, the book includes coverage of:* special educational needs* attendance, truancy and exclusion* bullying and behavioural problems* management and administration* safety and security.There is also a review of up-to-date DfEE requirements and suggestions for further action and reading. The addresses of useful contacts help to make it a reference book no primary school should be without.